'There and back again': The Career of John Ramsay of Terrenzeane (C. 1464–C. 1513). (3rd July 2018) - Yorath, David M.
Abstract : War and military activity has always engendered espionage. Christine de Pisan's Fayttes of Armes advised its readers — kings and lesser rulers — to be 'curiose & diligent', and 'to send … here & there … espies subtyli … to understande the purpose of [the] enemy'. 1 England's fifteenth-century king, Edward IV, was a master of such practice, with his victories against the Scots and his capture of Berwick in 1482 owing much to a vast network of intelligence. His successor, Henry VII, also invested in the area and used a great many disaffected Scots, Picards and merchants for diplomatic and military gain. And, of this group, perhaps the most interesting and contemporaneously recorded is a Scottish nobleman, John Ramsay, Lord Bothwell and Lord Balmain, of Terrenzeane ( c . 1464– c . 1513). He is an individual often neglected by researchers, but who appears very much to have played an important role in shaping the histories of both kingdoms. The following article aims to trace his noteworthy career in the later medieval and early modern periods.